2016
DOI: 10.1590/1678-98652016000200004
|View full text |Cite
|
Sign up to set email alerts
|

Multiple risk behaviors for non-communicable diseases and associated factors in adolescents

Abstract: Objective: To estimate the prevalence of risk behaviors for non-communicable diseases and analyze their associated factors in adolescents. Methods: A school-based cross-sectional study was conducted in 2008 with 1,139 adolescents aged 14 to 19 years attending public and private high schools in Cuiabá, Midwestern Brazil. Data were collected using a selfadministered questionnaire, including a semiquantitative Food Frequency Questionnaire. The prevalence of tobacco smoking, alcohol experimentation, physical inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
2
13
0
1
Order By: Relevance
“…The high frequency of the co-occurrence of risk factors for NTCDs (almost 70.0%), observed in this study, has also been described by other authors (ranging from 45.0% to 72.2%) [7][8][9][10][11][12][13][14]. However, comparison with the findings of those studies should be performed with caution due to the diversity in the risk behaviors assessed.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The high frequency of the co-occurrence of risk factors for NTCDs (almost 70.0%), observed in this study, has also been described by other authors (ranging from 45.0% to 72.2%) [7][8][9][10][11][12][13][14]. However, comparison with the findings of those studies should be performed with caution due to the diversity in the risk behaviors assessed.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, being a Caucasian adolescent and having private school education were considered markers of a better socioeconomic situation [31], and presented a higher chance of the co-occurrence of risk factors compared to the case of black/brown and public school students. Rodrigues et al [13], observed a similar relationship in adolescents from private schools of Cuiabá, Mato Grosso, while Tassitano et al [11] observed a higher chance of exposure to three or more risk behaviors, in adolescents with a higher family income. However, Silva et al [14], reported a lower chance of the clustering of risk factors among those whose mothers had a higher level of schooling.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…an association between alcohol consumption and tobacco use in adolescents (10,23). The determinants of this relationship are not well understood, however, the etiology of multiple psychoactive substances comorbidity indicates that substances such as alcohol and tobacco share common genetic and environmental factors (24).…”
Section: Brazilian Healthy Eating Index Revised (Bhei-r)mentioning
confidence: 99%
“…Moreover, it has been shown that certain risk behaviors increase the risk of involvement in others, forming clusters of behaviors (6)(7)(8), that is, the occurrence of concurrent risk behaviors in adolescents (9,10). Simultaneity of different risk behaviors may have a synergistic effect on the deterioration of individual health; in other words, it may result in a multiplicative deleterious effect, rather than an additive effect of each behavior (11).…”
Section: Introductionmentioning
confidence: 99%